Dynamics of an Invincible Troop Formation in Ancient Open Battlefields - Kishore Dutta (Interdisciplinary Description of Complex Systems, 2021)
One of the most enthralling ancient magical battle formation tactics is the Chakravyuh -- a multilayer dynamic defensive structure, which was used in the 18-days long Kurukshetra war as described in the great Indian epic Mahabharata and in many subsequent scriptures. Unfortunately, none of the existing literature address its inner details or the skills involved and, as such, its working still shrouds in mystery. What makes it nearly invincible even for an exceptionally skilled warrior? How a huge troop was controlled, organized, and restructured from the core of the Chakra? What are the governing rules for maintaining the structure even in the time of extreme hardship in the battlefield? In quest of the answers to such technical questions, while we made attempts to explore and decipher the inner details of Chakravyuh, we find some descriptions that differ geometrically from each other. Despite such variants of the structure, here we would like to bring into focus the common inner mechanism of such a multilayer organizational strategy that, in turn, confirms its inherent geometry. It reveals how, because of synchronize maneuvers, the direction of rotation of the Chakra about its axis is closely interwoven with the direction of movement of the infantrymen. The fact that relative spinning motion has adverse psychological impact in diminishing mental power, seems to be the foremost principle behind the design of its dynamics that slowly push on an invading warrior towards one of the dead-ends that are created by restructuring the Chakra out of nearly infinite possible ways.